Efficacy and safety of SPRINT and STAR protocol on Malaysian critically-ill patients - Ahamad, Nurhamim; Abdul Razak, Normy Norfiza; Jamaludin, Ummu Kulthum; Suhaimi, Fatanah M.; Pretty, Christopher G.; Chase, Geoffrey; Md Ralib, Azrina; Mat Nor, Mohd Basri (IEEE, 2017)
Abstract—Intensive care unit patients may have a better glycaemic management with the right control protocol. Results of virtual trial performance on Malaysian critically-ill patients adopting a model-derived and model-based control protocol known as SPRINT and STAR are presented in this paper. These ICU patients have been treated by intensive sliding-scale insulin infusion. The effectiveness and safety of glycaemic control are then analysed. Results showed that patient safety improved by 83% with SPRINT and STAR protocol as the number of hypoglycaemic patients significantly reduced (BG<2.2 mmol/L). Percentage of time within desired bands and median BG improves in both SPRINT and STAR. However the improvements are associated with higher number of BG measurements (workload).